Second-hand tobacco smoke in public places in urban and rural China. Issue 4 (24th July 2007) - Stillman, Frances; Navas-Acien, Ana; Ma, Jiemin; Ma, Shaojun; Avila-Tang, Erika; Breysse, Patrick; Yang, Gonghuan; Samet, Jonathan
Abstract : Objective: To assess airborne nicotine concentrations as an indicator of second-hand smoke (SHS) exposure in public places in both urban and rural areas of China. Design: Measurement of vapour-phase nicotine concentration using a common protocol in all locations. A total of 273 samplers were placed for 7 days in urban and rural areas of China, including Beijing and the capital city, and a county (rural) area of the following provinces: Sichuan (Chengdu/Mianzhu), Jiangxi (Nanchang/Anyi) and Henan (Zhengzhou/Xin'an). Setting: Samplers were placed in hospitals, secondary schools, city government buildings, train stations, restaurants and entertainment establishments (internet cafes, mahjong parlours and karaoke bars) in each location. Main outcome measure: The time-weighted average airborne concentration of nicotine (μg/m 3 ) was measured by gas chromatography. Results: Airborne nicotine was detected in 91% of the locations sampled. Beijing had the highest nicotine concentrations in most indoor environments (median 3.01 μg/m 3 ) and Chengdu had the lowest concentrations (median 0.11 μg/m 3 ). Overall, restaurants and entertainment establishments had the highest nicotine concentrations (median 2.17 and 7.48 μg/m 3, respectively). High nicotine concentrations were also found in government buildings and in train stations. Conclusions: The data collected in this study provide evidence that SHS exposure is frequent in public places in China. Environmental nicotine concentrations in China provide evidence for implementation and enforcement of smoke-free initiatives in public places in China and indicate the need for protecting the public from exposure to SHS.